Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 167483080 species occurrences available in GBIF matching the query: { "BasisOfRecord" : [ "is Specimen" ] } The dataset includes 167483080 records from 12360 constituent datasets: 303 records from National Botanic Garden Belgium - Martius. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 20084 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 8328 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 173 records from UWIZM Anoles. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 25 records from Novas Espécies De Acrosternum Subgênero Chinavia (Heteroptera, Pentatomidae, Pentatomini). 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 74123 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 2451 records from Macrobenthos Chukchi Sea, 1986. 4269 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 10 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 5 records from Note on the genus Lecanophryella (Ciliophora: Suctorea) with description of a new species from west coast of India. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 28468 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 607514 records from Plant. 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 13162 records from Observations du Conservatoire botanique national du Bassin parisien.. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 12859 records from Colecção Entomológica IIA. 4 records from Rediscovery of Lustrina Kurian (Hymenoptera, Chrysididae), with redescription of L. assamensis Kurian. 110350 records from TNHC Herpetology Collection. 89 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 108 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 4681 records from Museu Darder de Banyoles. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 11 records from More new Diplotrema earthworm species from southern Mexico (Annelida, Crassiclitellata, Acanthodrilidae, Acanthodrilinae). 316 records from Moss species from Heard Island, 1987 and 2000. 7123 records from DMNS Egg Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 146 records from Colección de moldes endocraneanos del CENPAT. 1095 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 2 records from Re-evaluation of the morphology of the monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999 (Annelida, Phyllodocida, Nereididae). 914 records from Collection Meebold HBG Herbarium. 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 7 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 54910 records from Herbarium Universitatis Daugavpiliensis. 5 records from Some Cheilostomata (Bryozoa) from the Java Sea, central Indonesian Archipelago with a description of Pleurocodonellina jeparaensis n. sp. (Smittinidae). 30952 records from SANT-Algae. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 16542 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6237 records from Plecoptera. 22 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 5 records from Amphibia, Bokermannohyla nanuzae, Scinax curicica, Leptodactylus camaquara, Physalaemus evangelistai, and Proceratophrys cururu: Distribution extensions. 3 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 3 records from Revision of the genus Exsuperantia Özdikmen, 2009 (Tetractinellida: Phymaraphiniidae) with description of a new species from the Atlantic Ocean. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 6 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 13736 records from MfN - Mallophaga Collection. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 609 records from Collection botanique Mulon L. (BOUM). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 5 records from Garra roseae, a new species from the Makran region in southern Iran (Teleostei: Cyprinidae). 439 records from Implementación de la bioindicación en el Río Magdalena. 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 50873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 279731 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 5 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 5 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 3035 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 878 records from COA Bird Collection (Arctos). 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 1 records from A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus. 22857 records from National Botanic Garden Belgium - Myxomycetes. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 66 records from Trogonoptera brookiana mollumar d’Abrera, Doggett & Parker, 1976 (Lepidoptera: Papilionidae), a subspecies or a synonym?. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 318235 records from CAS Herpetology (HERP). 92 records from Review of Thoreyella Spinola with the description of two new species from Brazil (Heteroptera, Pentatomidae). 43165 records from Butler University Friesner Herbarium (BUT). 255225 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 5514 records from MCP-Aves - Coleção de Aves. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 12557 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 20 records from Two Hexapleomera species from Japan, with a new species description and discussion of phylogenetic relationships within Hexapleomera (Crustacea: Tanaidacea). 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 23 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 869 records from Vertebrados terrestres de San Juan de Camarones, Durango. 142 records from Botanical collection of the National Museum. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 404 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 118451 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3184 records from Herbarium specimens of Limoges university (LIMO). 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 105857 records from Fish specimens of Kagoshima University Museum. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13647 records from UTEP Invertebrates (Arctos). 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 1798 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 5 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 44 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 4 records from Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru. 521 records from Tentaculata collection of National Museum of Nature and Science. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 10720 records from Mollusca specimens of Ryukyu University Museum (Fujukan). 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 573 records from Centre for Plant Medicine Research (CPMR) medicinal plants dataset. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 833709 records from AMNH Bird Collection. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 1353 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 689 records from BioBlitz Barcelona 2010-14. 5890 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 21 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 116461 records from Naturalis Biodiversity Center (NL) - Crustacea. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 5 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 41100 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 13 records from New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 798 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 31 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 649 records from Beetles from nature reserves and nearby forests in Østmarka. 1667 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 2044 records from The Broward College Insect Collection. 4975 records from Radiolaria specimens from the Norwegian Sea and Arctic Ocean. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 19 records from Distribution Data for Megachile chomskyi. 24283 records from Berea College, Ralph L. Thompson Herbarium. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 59626 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 597 records from Eriophyoid Mites of Poland. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 2274 records from Weber State University Herbarium. 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 2 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 855 records from Museu_Paraense_Emilio_Goeldi_Microfosseis_Collection. 1 records from On the Chilopoda from Turkey. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 6 records from New Species of Neotibilis Grazia & Barcellos (Hemiptera: Pentatomidae: Pentatomini). 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 446 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 2 records from Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana. 1333 records from Sistematización de la colección de peces del centro de México. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 62125 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1158 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 26 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 2 records from Contribution to the knowledge of Himalayan and North Indian species of Scaphidium (Coleoptera, Staphylinidae). 61 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 1957 records from SIM-Fungal records compiled by Joan Montón. 9090 records from Plant specimens of Obihiro Centennial City Museum. 783924 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 3 records from Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 9120 records from ICEL (Land - Invertebrates). 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 34 records from NZCS Brownsberg Nature Park Monitoring. 3652 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 60885 records from Collection Mollusca SMF. 10 records from Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae). 12681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 20 records from Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 1289 records from Records of the Victorian Conservation Seedbank. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 119366 records from The digitization of plant specimens of NTU. 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 1952 records from ISM Ichthyology Collection. 2 records from Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 8259 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 108701 records from The Himalayan Uplands Plant database (HUP Version 1). 8 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 1897 records from Royal BC Museum - Herpetology Collection. 5 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 29340 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 7918 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 7 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 29 records from New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 1 records from Norwegian Lepidoptera working group. 11 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 10 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 2 records from Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 6202 records from Lichens of North-Eastern Poland. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 32 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6 records from Exogoninae (Annelida: Syllidae) from Chilean Patagonia. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 119 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 270 records from bmhs_weatherheadshell_collection. 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 555992 records from flora&fauna(NIBR)2019. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1793 records from Herbarium BSG Lichenes. 6 records from Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) a new parasitic nematode from a Japanese polydesmid millipede (Polydesmida: Xystodesmidae). 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 28558 records from University of California Santa Barbara Invertebrate Zoology Collection. 5253 records from Colección de Laurales, Liliales, Lycopodiales, Magnoliales y Malpighiales del Museo Botánico CORD - IMBIV. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 1156 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 13 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 463 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 1 records from Synchiropus sycorax, a new species of dragonet from the Philippines (Teleostei: Callionymidae). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 66196 records from Entomology Collection at the Natural History Museum of Utah. 1552 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 28843 records from UTEP Herpetology (Arctos). 14573 records from Biological Reference Collections ICM CSIC. 245 records from A review of Tersilochinae (Hymenoptera: Ichneumonidae) of Finland. Part 1: taxonomy. 6 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 22 records from Review of Aphidiinae parasitoids (Hymenoptera: Braconidae) of the Middle East and North Africa: key to species and host associations. 349178 records from AMNH Herpetology Collections. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 15633 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 616 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 404259 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 8 records from Description of the helminth communities of sympatric rodents (Muroidea: Cricetidae) from the Atlantic Forest in northeastern Argentina. 374 records from Ichthyologie ZMK. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 12 records from Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae). 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 8363 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 11 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 34 records from A New Species Of Apostenus From California, With Notes On The Genus (Araneae, Liocranidae). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 17 records from Morphology and DNA barcodes of two species of Bradysia Winnertz from China (Diptera, Sciaridae), with the description of Bradysia minorlobus Yang, Shi & Huang sp. n.. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 13 records from A new species and a key to world species of the flavipes species-group of the genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) from Japan. 18 records from Mammals in MZNA-VERT: project Loza. 5 records from A revision of the genus Saccoglossus (Hemichordata: Enteropneusta: Harrimaniidae) with taxonomic descriptions of five new species from the Eastern Pacific. 5 records from New species of the snakefly genus Mongoloraphidia (Raphidioptera: Raphidiidae) from China. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 27 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 1798 records from Insect (KIDR-IN). 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 27 records from An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea). 62 records from New species of Cirratulidae (Annelida, Polychaeta) from abyssal depths of the Clarion-Clipperton Fracture Zone, North Equatorial Pacific Ocean. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 5 records from Morphological and molecular characterisation of Discotylenchus lorestanensis sp. n. (Nematoda: Tylenchidae) from Iran. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 2864 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 4 records from Critical Checklist of the Indian species of Hypogastrura (Collembola: Hypogastruridae) with a description of a new species from Satkosia Wild Life Sanctuary. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 115 records from Mammalians Specimens of Akita Prefectural Museum. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 4 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 6723 records from Los mamíferos del estado de Durango, México. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 7 records from New species of Xiphoniscus and new record of Androdeloscia escalonai (Isopoda, Scutocoxifera, Oniscidea, Philosciidae) from Brazilian Amazon. 136 records from Occurrence data of some marine invertebrates and freshwater crabs housed in the natural history collection at the National Museums of Kenya. 14 records from A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species. 102601 records from MSB Fish Collection (Arctos). 8 records from Two remarkable new species of Argyrophorus Blanchard from the Peruvian high Andes (Lepidoptera, Nymphalidae, Satyrinae). 5 records from A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 5 records from Reduced antennal segmentation in a new species from Iran of the genus Aeolothrips (Thysanoptera: Aeolothripidae). 1 records from Key to genera of Chinese Coelidiinae leafhoppers, with description a new species of the leafhopper genus Baseprocessa (Hemiptera: Auchenorrhyncha: Cicadellidae). 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 21 records from A new genus of Theraphosid spider from Mexico, with a particular palpal bulb structure (Araneae, Theraphosidae, Theraphosinae). 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 6 records from New species of oribatid mites of the family Oppiidae (Acari, Oribatida) from Chile. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 6 records from New species and records of the pseudoscorpion genus Geogarypus (Pseudoscorpiones: Geogarypidae) from India, Sri Lanka and New Guinea. 1195 records from edibleinsects. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 7300 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 19 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 16 records from The genus Trichorhina Budde-Lund in Brazil, with description of seven new species (Isopoda, Oniscidea, Platyarthridae). 3 records from The pseudoscorpion genus Verrucachernes (Pseudoscorpiones: Chernetidae) in the Indian region. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 7873 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 3 records from Moenkhausia restricta, a new species from the upper Rio Negro, Amazon basin, northwestern Brazil (Characiformes: Characidae). 10072 records from Guadeloupe_Herbier. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 24 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 5 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 17 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1873 records from Odonata de la huasteca potosina (insecta). 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 29 records from Herbarium Senckenbergianum (FR) - Protista. 116 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 13 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 1 records from The Little Harlequin Katydid-a new species of Paraxiphidium Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Conocephalini) from the Amazonian Rainforest. 1 records from Oribates humeralis. 175 records from PSUZC-Rodents Collection. 33 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 3 records from Zoology in the Middle East. 4 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 16258 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 12 records from Neoplasta Coquillett (Diptera: Empididae: Hemerodromiinae) from Brazil: new species and male description of N. fortiseta Smith. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1 records from First description of the male of Oxythrips tristis Bagnall (Thysanoptera: Thripidae). 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 10 records from Echinodera (Ruteria) soumasi sp. n. from Greece (Coleoptera, Curculionidae). 82 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 1 records from A new species of the hairy crab genus Pilumnus (Decapoda: Brachyura: Pilumnidae) from Belize. 93 records from Descriptions of two new species of Brachyzapus Gauld & Dubois (Hymenoptera: Ichneumonidae: Pimplinae) from South Korea with key to a Palaearctic species. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 10 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 58 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 3 records from A new species of highland vampire crab (Crustacea: Brachyura: Sesarmidae: Geosesarma) from Serian, Sarawak. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 93 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 11473 records from SMDB - Santa Maria Departamento de Biologia. 53207 records from Naturalis Biodiversity Center (NL) - Diptera. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 13981 records from Flora of the Korean Peninsula. 235 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 1 records from Berlese's Primitive Oribatid Mites. 3 records from Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species. 159 records from Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1562 records from Plathelminthes - SMF. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 13483 records from Insect specimens of Rikuzen-Takata City Museum. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 18 records from A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini). 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection. 18940 records from Cowan Tetrapod Collection - Mammals. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 110 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 34 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 50344 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 139635 records from ARABEL - Arachnologia Belgica. 13 records from Papuacocelus papuanus n. gen., n. sp. a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae). 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 174 records from Antarctic pycnogonids. 18699 records from LSUMZ (LSU MNS) Fishes Collection. 62776 records from MLZ Bird Collection (Arctos). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 11 records from A new species of Trachylepis (Squamata: Scincidae) from Central Africa and a key to the Trachylepis of West and Central Africa. 1997 records from Lichen collection. 356 records from UWYMV Herpetology Collection (Arctos). 2 records from A new species of the subgenus Duolandrevus (Eulandrevus) Kirby, 1906 from Guangxi, China (Orthoptera: Gryllidae: Landrevinae). 92061 records from Herbarium (ICEL). 104997 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Zetes ephippiatus. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 13 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 15827 records from Leiner-Herbar Konstanz. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2007 records from Plant specimens of Bihoro Museum. 105 records from bmhs_moth_collection. 4020 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 47 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 106 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 51 records from Anfibios y reptiles de la expedición en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 394 records from Reptilia ZMK. 17581 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 405 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 2 records from A new gastropod associated with a deep-sea whale carcass from São Paulo Ridge, Southwest Atlantic. 46865 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 26841 records from MSUM Ichthyology and Herpetology Collections. 5 records from Didogobius janetarum sp. nov., a new cryptobenthic goby species from the Cape Verde Islands (Teleostei: Gobiidae). 9 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 1 records from A new species of Bathynomus Milne Edwards, 1879 (Isopoda: Cirolanidae) from The Bahamas, Western Atlantic. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 123 records from Luciogobius yubai, a new species of gobioid fish (Teleostei: Gobiidae) from Japan. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 1 records from Myolaimus ibericus sp. n. (Nematoda, Rhabditida, Myolaimidae) from southern Iberian Peninsula, with a key to species of the genus. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 3326 records from Plant specimens of Nasunogahara Museum. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 62210 records from Tiroler Landesmuseum Ferdinandeum. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9446 records from Colección de Mamíferos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-M). 2 records from New species of the Genus Haliclona (Haplosclerida: Chalinidae) from Korea. 854 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 23 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 450 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 78 records from Mammals (GNHM-MM). 4591 records from WII Herbarium Dataset. 1889 records from Diatomeas bentónicas de los oasis de Baja California Sur. 32469 records from Quaid-i-Azam University Herbarium. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 25 records from Two new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Shevaroy massif, Tamil Nadu, India, with a preliminary ND 2 phylogeny of Indian Cnemaspis. 2 records from A new species of cascade frog (Amphibia: Ranidae) in the Amolops monticola group from China. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 6 records from Description of Lacon mertliki sp. nov. (Coleoptera: Elateridae: Agrypninae) from the Hyrcanian forest ecoregion, with a key to the Lacon species of Iran. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 9 records from Description of two new species of Magnispina and a new hypothesis of phylogenetic relationships for Heteropachylinae (Opiliones: Laniatores: Gonyleptidae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 14 records from Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 2 records from The origin and evolution of the Tyrannosaurids, Part 1. 442 records from Specimen references on the Rubiaceae family held by theTAN Herbarium. 4 records from Bioacoustics and morphology of a new bush-cricket species of the genus Isophya (Orthoptera: Phaneropterinae) from Turkey. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 41 records from A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru. 660 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202439 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 62198 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 1 records from A new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 1 records from Pritchardia boliviensis N. Gen., N. Sp. (Anoplocephalidae: Linstowinae) a tapeworm from opossums (Didelphidae) in the yungas and lowlands of Bolivia and Atlantic forest of Paraguay. 4 records from Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula). 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 4049 records from Estudio taxonómico distribucional de los peces del estado de Chiapas, México. 1241 records from Vertebrate collections of the Department of Animal Biology and Conservation Sciences, University of Ghana. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 80 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 408 records from Antarctic and SubAntarctic Ophiuroidea - MNA (Section of Genoa). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 5 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 1 records from A new species of the genus Larutia (Squamata: Scincidae) from Gunung Penrissen Sarawak, Borneo. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 6 records from A new species of Hygrogeus Mulsant & Rey, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from Xizang, China. 1872 records from Herbier National de Guinée (HNG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 300 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 182 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 6 records from On the Chilopoda from Turkey. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 3621 records from Millenium Seedbank (MSB). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 20941 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 3 records from Ditylenchus sarvarae sp. n. (Tylenchina: Anguinidae) from Iran. 15 records from NOTE SU ALCUNE SPECIE DEL GEN. EUPOLYBOTHRUS DELLA FAUNA DI GRECIA (Chilopoda, Lithobiomorpha). 24 records from Revision of the Diplommatinidae (Gastropoda: Cyclophoroidea) from Java. 250422 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 4 records from Two new genera for the Botyodes species complex (Lepidoptera: Pyraloidea: Crambidae). 1486 records from Crustacea ZMK. 81 records from Revisão Do Gênero Runibia (Heteroptera, Pentatomidae, Pentatomini). 1 records from New hosts and localities for species of Cancricepon Giard & Bonnier, 1887 (Isopoda: Epicaridea: Bopyridae) with description of two new species and comments on the relationship between Cancricepon and Trapezicepon Bonnier, 1900. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 5 records from The genus Eremiothrips (Thysanoptera: Thripidae) from China, with one new species. 1 records from 3. Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 5615 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 6 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 16 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 22 records from Redescription of the genus Koumansetta (Teleostei: Gobiidae), with description of a new species from the Red Sea. 1 records from First record of family Dipsocoridae (Hemiptera: Heteroptera: Dipsocoromorpha) from the Korean Peninsula and a new generic combination for Cryptostemma japonicum Miyamoto. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 289591 records from Allan Herbarium (CHR). 254268 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 26 records from Schwedische Oribatei (Acari). III.. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1 records from Hypochthonius rufulus. 21 records from Nomenclatural changes and lectotype designations in the seed-beetle genus Sennius Bridwell: with the synonymization of Megasennius Whitehead & Kingsolver (Coleoptera: Chrysomelidae: Bruchinae). 18656 records from Coleção Entomológica Moure e Costa. 6 records from New records of benthic hydroids (Cnidaria: Hydrozoa) from the coast of Oaxaca, Mexico. 13 records from Taxonomic notes on genus Coelotrypes Bezzi (Diptera: Tephritidae: Trypetinae) with description of two new species. 2 records from A new species of the subgenus Tachycines (Tachycines) (Othoptera: Rhaphidophoridae) from Guizhou, China. 8 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 5 records from A new Oreonetides Strand, 1901 from the Russian Far East (Araneae, Linyphiidae). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 7 records from Revision of the Afrotropical genus Susua Lugo-Ortiz & McCafferty 1998 (Ephemeroptera: Baetidae: Protopatellata). 80622 records from SA Flora (BDBSA). 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 19 records from Feather mites of the genera Dubininia and Cacatualges (Acari: Xolalgidae) associated with parrots (Aves: Psittaciformes) of the Old World. 7 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 39 records from A review of all Recent species in the genus Novocrania (Craniata, Brachiopoda). 1 records from Celaeno coccinea. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 28108 records from Marie-Victorin Herbarium (MT) - Bryophytes. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 15 records from Free-living nematodes of the genus Syringolaimus de Man, 1888 (Nematoda, Enoplida, Ironidae) from the Angola Basin, South-East Atlantic Abyss. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 22 records from On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 1 records from A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae). 616 records from martius-munchen-infocomp. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 7 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 8109 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 14510 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 8704 records from HSU Wildlife Birds. 14 records from The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus). 1371 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 3158 records from Utah State University, Intermountain Herbarium. 866 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 2998 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 119382 records from Mammalogy Collection - Royal Ontario Museum. 10 records from A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 867 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 251165 records from CAS Entomology (ENT). 39614 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 8364 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 4 records from Pycnogonidea specimens of Kuroshio Biological Research Foundation. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 13 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 1 records from Mites of the family Parasitidae Oudemans, 1901 (Acari: Mesostigmata) from Japan: a new species of Vulgarogamasus Tichomirov, 1969, and a key to Japanese species. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 5582 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from Geographically structured genetic variation in Ptychozoon lionotum (Squamata: Gekkonidae) and a new species from an isolated volcano in Myanmar. 4 records from A new species of Sarcofahrtiopsis (Insecta, Diptera, Sarcophagidae) from mangrove forests in the Brazilian Amazon, with a key to species identification. 14842 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 5 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 1 records from A new species of the mud shrimp genus Axianassa Schmitt, 1924 (Decapoda: Gebiidea: Laomediidae) from the Ryukyu Islands, southern Japan. 3 records from Channa aurantipectoralis, a new species of snakehead from Mizoram, north-eastern India (Teleostei: Channidae). 108313 records from Arizona State University Hasbrouck Insect Collection. 2 records from From an old sound recording to a new species in the genus Horatosphaga (Orthoptera: Tettigonioidea: Phaneropterinae: Acrometopini). 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 39 records from Integrating data to redescribe Euschistus taurulus Berg (Hemiptera: Pentatomidae). 40 records from Taxonomic review of Dendrophryniscus brevipollicatus Jiménez de la Espada, 1870, with revalidation of D. imitator (Miranda-Ribeiro, 1920) and D. lauroi Miranda-Ribeiro, 1926, and description of four new related species (Anura, Bufonidae). 8 records from A new species of the genus Chrysacris Zheng, 1983 from China (Orthoptera: Acridoidea, Acrididae). 140 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 19329 records from Flora of the Korean Peninsula Phase II. 3381 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 25 records from Taxonomic revision of the genus Hirotophora Brown et al. (Diptera: Phoridae) with the description of a new species from Chile. 1 records from A new species and a new record of genus Hexacentrus Serville, 1831 (Orthoptera: Tettigoniidae: Hexacentrinae) from India. 4 records from Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 7 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 7 records from Description of two new and two known species of the Genus Tylencholaimellus Cobb in M. V. Cobb, 1915 (Nematoda: Dorylaimida: Tylencholaimoidea). 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 5696 records from R-Bryophyta - Herbário do Museu Nacional - Bryophyta. 1 records from A new Indian record and morphological variation for Eulimnadia khoratensis Rogers et al., 2016 (Crustacea: Branchiopoda: Spinicaudata). 46057 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 3 records from A new species of Coriella, Coriella chernyshevi n. sp. (Entoprocta, Barentsiidae), with comments on the genera Coriella and Pedicellinopsis. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 94 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 3265 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 190 records from Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex.. 3 records from Nomenclature and synonymic remarks on two species of Eupterotidae (Lepidoptera) described by Johan Christian Fabricius, and notes on related species. 5 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 3 records from A new species of stone loach (Teleostei: Nemacheilidae: Schistura) from Arunachal Pradesh, India. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10898 records from Inventario de Hymenóptera; parasítica en México. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 4639 records from UAM Herbarium (ALA), Algae Collection (Arctos). 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 58368 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 16 records from Endemism and long distance dispersal in the waterfleas of Easter Island. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 36 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 3004 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 877 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 9 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 66 records from The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision.. 77 records from Distribución del gecko introducido Hemidactylus frenatus (Dumeril y Bribon 1836) (Squamata: Gekkonidae) en Colombia. 124 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 3 records from Sinorhodeus microlepis, a new genus and species of bitterling from China (Teleostei: Cyprinidae: Acheilognathinae). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3712 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 817 records from Lucanidae. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2745 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 24795 records from Université d'Aix-Marseille. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 4 records from Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 269448 records from Vascular Plant Specimen database of Kanagawa Prefectural Museum of Natural History. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 13 records from Revision of the genus Setosella (Bryozoa: Cheilostomata) with description of new species from deep-waters and submarine caves of the Mediterranean Sea. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 32 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 5 records from Pseudanthias emma new species, with notes on a collection of anthiadine serranid fishes from off Myanmar (eastern Indian Ocean). 8784 records from Bryophytes specimens of Akita Prefectural Museum. 331 records from Administración Nacional de Institutos y Laboratorios de Salud. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 80123 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 2414 records from UWYMV Bird Collection (Arctos). 11994 records from Hatikka Observation Database. 1000 records from Diplopoda (JJHA-DI). 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 20 records from A new species of sardine, Sardinella electra (Teleostei: Clupeiformes: Clupeidae), from the Ryukyu Islands, Japan. 17444 records from CAS Entomology Type (TYPE). 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 103176 records from MfN - Heteroptera Collection. 5 records from Five new species of the genus Primulina (Gesneriaceae) from Limestone Areas of Guangxi Zhuangzu Autonomous Region, China. 354 records from Sponges of the Guyana Shelf. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 2476 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 11607 records from MBML-Anfibios - Coleção de Anfíbios MBML. 119 records from Kinorhyncha. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 1618 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 1 records from A new genus of the Tympanophorus lineage of the subtribe Anisolinina from Madagascar (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 140 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 16 records from A new species of Tropidophorus Duméril & Bibron, 1839 (Squamata: Sauria: Scincidae) from Sarawak, East Malaysia (Borneo). 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 298 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 15856 records from CHAS Ornithology (Arctos). 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5780 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 5 records from Two new species of the genus Unaspis MacGillivray, 1921 (Hemiptera: Coccomorpha: Diaspididae) from China. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 173 records from Barcant Butterfly Collection - Papilionidae. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 3 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 4 records from Taxonomic updates for some confusing Micronesian species of Camponotus (Hymenoptera: Formicidae: Formicinae). 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 18 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 10075 records from Nematoda of Costa Rica (INBio). 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 4 records from A new Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae), from the eastern part of the Upper Guinea biodiversity hotspot, West Africa. 4 records from Description of four new species of the Cirolana ‘ parva group’ (Crustacea: Isopoda: Cirolanidae) from Thailand, with supporting molecular (COI) data. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 170 records from The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874). 1 records from VANILLA RIVASII (ORCHIDACEAE), A NEW SPECIES FROM THE COLOMBIAN PACIFIC REGION. 9 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 7242 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 6 records from Review of the genus Cruziohyla (Anura: Phyllomedusidae), with description of a new species. 554 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 352976 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 26 records from A new species of Phrynus Lamarck, 1801 (Arachnida: Amblypygi), from Trinidad and Tobago, and Venezuela, with a redescription of Phrynus pulchripes (Pocock, 1894). 100 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 150 records from Museu Paraense Emílio Goeldi - Crocodylia Collection. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 82855 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Feathers_and_Skin. 9 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 22 records from Collection Mantodea - SMF. 1201 records from Monocotyledonous Geophytes of Fergana Valley. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 86 records from UWIZM Cnidarians. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from A new species of the spider genus Solenysa from China (Araneae, Linyphiidae). 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 11 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 6 records from On the systematics of the water mites Hygrobates nigromaculatus Lebert, 1879 and H. setosus Besseling, 1942 (Acari, Hydrachnidia, Hygrobatidae). 87279 records from Taiwan Forestry Research Institute. 1115 records from Carabid Collection (Pinned Vouchers). 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 31229 records from DIPOL. 1800 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Mastozoología. 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40333 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 20287 records from UAM Invertebrate Collection (Arctos). 18 records from The genera and species of Comatulidae (Comatulida: Crinoidea): taxonomic revisions and a molecular and morphological guide. 11 records from A new genus of Pexicopiini (Lepidoptera: Gelechiidae) for “ Gelechia ” acanthopis Meyrick, 1932, with review of functional morphology of male genitalia in allied genera. 4 records from Discovery of the first pincer wasp (Hymenoptera, Dryinidae) from Rovno amber. 10 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 4 records from Arthropoden aus südostalpinen Höhlen.. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 266 records from Revision of the genus Doryscus Jacoby (Coleoptera: Chrysomelidae: Galerucinae). 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 215 records from Marine Plants (NHMC-SA). 68 records from New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18224 records from K-State Museum of Entomological and Prairie Arthropod Research. 3 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 638 records from Diversidad y distribución geográfica de las especies de culícidos de importancia médica en la región centro-occidental de México. 7 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 57 records from The Ascidiacea collected during the 2017 British Columbia Hakai MarineGEO BioBlitz. 2 records from Review of amphipods of the genus Cryptodius Moore, 1992 (Amphipoda: Ochlesidae) from the coastal waters of Sakhalin Island (Far East of Russia). 2 records from A new addition to the subfamily Anabropsinae (Orthoptera: Anostostomatidae) from China. 18 records from Two new genera of Oriental xyleborine ambrosia beetles (Coleoptera, Curculionidae: Scolytinae). 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 31 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 41 records from Registros Primates Neotropicales Convocatoria APC. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 3110 records from Herpetile collection NTNU University Museum. 3 records from Taxonomic review of the genus Urostylis (Hemiptera: Heteroptera: Urostylididae) from the Korean Peninsula, with description of a new species. 3002 records from Colección de Peces Universidad Católica de Oriente. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 641 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 47 records from Two new species of Oxynoemacheilus from the Tigris drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae). 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 18 records from Aves de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 11 records from A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia. 1 records from The genus Alphocoris in the Indomalaya (Hemiptera: Heteroptera: Scutelleridae). 11622 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 5 records from New species of the non-biting midges of Tribe Chironomini (Dptera, Chironomidae) from the Bolshekhekhtsyrsky Reserve (Russia, Khabarovsk Territory). 4 records from Two new species of Podonomus Philippi (Diptera: Chironomidae: Podonominae) from mountains of Southeastern Brazil. 216 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 106 records from Coloration variability of the Oriental genus Agnorimus Miyake & Iwase, 1991 (Coleoptera: Scarabaeidae, Cetoniinae) with synonymic notes. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 37986 records from rmca-albertine-rift-cichlids. 62 records from Revision of the Madagascan genera Oncodopus Brongniart and Colossopus Saussure (Orthoptera: Tettigoniidae: Conocephalinae; Euconchophorini), with description of Malagasopus gen. nov.. 66 records from First catalogue of the Asopinae (Hemiptera, Pentatomidae) from French Guiana. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 2 records from Phylogeography of the endangered sand dune whiptail lizard Glaucomastix abaetensis (Dias, Rocha & Vrcibradic, 2002) with the description of a new species. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 3181 records from Colección de Rosales, Salviniales, Santalales, Sapindales, Saxifragales, Schizaeales y Selaginellales del Museo Botánico CORD - IMBIV. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 18 records from Six new species of Otacilia from southern China (Araneae: Phrurolithidae). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 307 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1490 records from Donación de la base de datos del Dr. Ortega Paczka resultados de la computarización de datos de colecta de muestras de maíz y otros cultivos asociados de diferentes regiones de México. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 3 records from Helobdella buzz n. sp. (Clitellata: Hirudinida), a bromeliad leech from the Brazilian Atlantic Forest. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 417 records from Sistemática del género Polianthes L (Agavaceae). 1889 records from Ims fish tag database. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 286 records from Catalogue of the primary types of marine molluscan taxa described by Tommaso Allery Di Maria, Marquis of Monterosato, deposited in the Museo Civico di Zoologia, Roma. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 12 records from The first record of Gnathostenetroididea Kussakin, 1967 from Australian waters with description of four new species of Gnathostenetroides Amar, 1957 (Crustacea: Isopoda: Asellota) from the Great Barrier Reef. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 404842 records from Texas A&M University Insect Collection. 214 records from Insectarium René-Martineau (IRM). 4 records from New information on the skipper fauna of Guangxi, China (Lepidoptera, Hesperiidae). 10000 records from Herbarium of Shinshu University. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 4400 records from USAC Mammals Collection. 349610 records from KUBI Herpetology Collection. 6 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 5 records from A new genus and species of Neotropical Nemobiinae (Insecta: Orthoptera: Grylloidea: Trigonidiidae: Nemobiinae). 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 9 records from World’s northenmost and rarely observed Nudibranchs: three new Onchidoridid species (Gastropoda: Doridida) from Russian seas. 1 records from Redescription of the poorly known pea crab, Pinnixa plectrophoros Glassell, 1935 (Decapoda: Pinnotheridae), from the Gulf of California. 2 records from Two new species of Biantes from China and Malaysia (Opiliones: Laniatores: Biantidae). 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 5 records from A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 4 records from The Chinese species of the genus Phlaeopterus Motschulsky, 1853 (Coleoptera Staphylinidae: Omaliinae: Anthophagini). 29 records from Revision of the enigmatic Southeast Asian spider genus Savarna (Araneae, Pholcidae). 6 records from The discovery of Rock Geckos Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) in the Tanintharyi Region, Myanmar with the description of two new species. 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 155 records from The genus Tarsonemus Canestrini and Fanzago, 1876 (Acari: Heterostigmatina: Tarsonemidae) in East Azerbaijan, Iran, with a description of T. lenticulatus sp. nov. and re-description of T. annotatus Livshits, Mitrofanov and Sharonov, 1979. 17 records from A molecular phylogeny of Speonemadus Jeannel, 1922 with description of two new species from Morocco (Coleoptera: Leiodidae: Cholevinae: Anemadini). 8 records from Gergithoides Schumacher, 1915 in Vietnam, with two new species, and taxonomic notes on the genus (Hemiptera: Fulgoromorpha: Issidae). 4 records from First report of the genus Tettigonia Linnaeus (Orthoptera: Tettigoniidae: Tettigoniinae) and record of Tettigonia caudata caudata (Charpentier, 1842) from India. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 89 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 58 records from The mutillid wasps of the Dasymutilla paradoxa species-group (Hymenoptera, Mutillidae). 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 5769 records from Collection Echinodermata SMF. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 2293 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 8 records from Two species of Ceradocus collected from coastal areas in Japan, with description of a new species (Crustacea: Amphipoda: Maeridae). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 49152 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 116 records from Deanophlebia: A new genus of south-eastern Australian mayflies and subsequent redefinition of the subgenus Nousia (Australonousia) (Ephemeroptera: Leptophlebiidae). 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1001 records from Colección Hidrobiológica del Chocó. 15 records from Two new species of the genus Sinotilla Lelej, 1995 (Hymenoptera: Mutillidae), with notes on taxonomic characters. 9304 records from Echinoderm collection of National Museum of Nature and Science. 1 records from Oribates facula. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 37 records from COA Entomology Collection (Arctos). 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 20862 records from Collection Aves (bird skeletons) SMF. 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 2355 records from Colección Ictiológica del CENPAT-CONICET. 1287 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 6 records from Three new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 10 records from Description of Two New Species of Baeocera Erichson (Coleoptera: Staphylinidae: Scaphidiinae) from México. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 60 records from New State and Host Records for Agromyzidae (Diptera) in the United States, with the Description of Ten New Species. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 7 records from Two new species of comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) from Yunnan, China. 2 records from An enigmatic new genus of cyclostome braconid wasp (Hymenoptera: Braconidae) from New Zealand. 17 records from Fossil and Recent molluscan types in the Auckland War Memorial Museum. Part 2: Polyplacophora and Scaphopoda. 2648 records from University of Sindh Jamshoro Herbarium. 7 records from On the taxonomic validity of Indian ground spiders: I. Genus Scopoides Platnick, 1989 (Araneae: Gnaphosidae). 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 51 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 1 records from A new species of Amolops (Anura: Ranidae) from China, with taxonomic comments on A. liangshanensis and Chinese populations of A. marmoratus. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 4 records from Description of three new species of Encyrtidae Walker (Hymenoptera: Chalcidoidea) from India. 1460 records from Spermatophytes collection of Okinawa Prefectural Museum & Art Museum. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 16 records from bmhscoralcollection. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from A new species of the genus Mongolotettix Rehn, 1928 from Hubei, China (Acrididae, Acridoidea, Orthoptera). 289 records from bmhs_butterfly_collection. 8 records from Diversidad de bacterias fotótrofas en comunidades microbianas bentónicas de Bahía Concepción, BCS, México. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3 records from From marine caves to the deep sea, a new look at Caminella (Demospongiae, Geodiidae) in the Atlanto-Mediterranean region. 22 records from BIRDRACE Birding Bentheim. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 295 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2 records from Taxonomic review of Stictophaula (Orthoptera: Phaneropterinae) with the description of one new species from Brunei Darussalam. 4 records from On two genera of spiny Pudicinae (Nematoda: Trichostrongylina) parasites of the spiny rat Proechimys simonsi (Mammalia: Echimyidae) from Peru. 62485 records from EAC - Herbário Prisco Bezerra. 14 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 1140 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 75 records from Type material housed in the Carcinological Collection of the Museo de La Plata, Argentina. 13 records from Cnidaria ZMK. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 49302 records from Olga Lakela Herbarium, University of Minnesota Duluth. 5 records from A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae). 1 records from The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae). 29095 records from Collection Crustacea - ZMB. 9 records from Macrocydia divergens, a new genus and species of Grapholitini (Lepidoptera: Tortricidae: Olethreutinae) from Central America. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 1 records from A new species of Chiridurothrips Okajima from Miocene amber of the Dominican Republic (Thysanoptera: Phlaeothripidae). 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 92 records from Ricinulei Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 4 records from Taxonomic study of the genus Meganola (Lepidoptera, Nolidae, Nolinae), with three new species and a new record from China. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 87 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 12649 records from Herbario CTES Plantas Vasculares. 1448 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 5 records from Settlement of the classification of Svistella Gorochov and Paratrigonidium Brunner von Wattenwyl using morphology and molecular techniques, with the description of a new species from Yunnan, China (Orthoptera: Trigonidiidae: Trigonidiinae). 9 records from Cephalaspidomorphs Specimens of Akita Prefectural Museum. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 6 records from Distribution of two species of Nephropsis Wood-Mason, 1872 (Crustacea, Decapoda, Nephropidae) from northeastern Brazil. 1397 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 154 records from Dermaptera in the icipe collection. 6 records from Tyrannosaurus and other Cretaceous carnivorous dinosaurs. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 30 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 3 records from The discovery, naming and typification of Limonium gmelini (Plumbaginaceae). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 467 records from Noctuidae brasileiros de importancia economica depositados na coleção MNHUK. 51 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 1923 records from Ibaraki Nature Museum, Birds collection. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1515 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 3 records from A new species of the genus Neobubastes Blackburn, 1892 from Western Australia (Coleoptera: Buprestidae: Buprestinae: Pterobothrini). 4 records from Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China. 7 records from Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 20 records from Heteroptera - SMNG. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 35865 records from Mollusca collection of National Museum of Nature and Science. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 110 records from Integrative revision of the Iberian species of Coscinia Hübner, [1819] sensu lato and Spiris Hübner, [1819], (Lepidoptera: Erebidae, Arctiinae). 24 records from Peces de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 42 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 24 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 7978661 records from NMNH Extant Specimen Records. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 2 records from Description of a new species of the genus Paraedes (Diptera: Culicidae) in Assam, India. 1 records from Upsa centennial, a new genus and species (Coleoptera: Scarabaeidae: Scarabaeinae: Endroedyolini) from the Southern Mistbelt forest in South Africa celebrating 100 years of entomology at the University of Pretoria. 15 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 51 records from The vespid fauna of Pakistan. 1 records from A new reticulated beetle (Coleoptera: Cupedidae) from Mexico with a catalogue of Cupedidae species of the world. 6859 records from Plan de vertebrados de la Patagonia. 13 records from A novel symbiotic relationship between mites and recluse spiders (Sicariidae: Loxosceles), with a description of a new Callidosoma species (Trombidiformes: Erythraeidae). 27 records from Jervois and Karinga Flora. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 15 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 3 records from Two new species of Tenuipalpus sensu stricto (Acari: Tenuipalpidae) from Brazil with a discussion on the ontogeny of leg setae. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 62283 records from PRECIS (KwaZulu-Natal Herbarium). 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 113 records from Caracterização do grupo Edessa rufomarginata e descrição de sete novas espécies (Heteroptera, Pentatomidae, Edessinae). 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 1760 records from Herbarium of the Prioksko-Terrasnyi Biosphere Reserve. 1 records from First report of the genus Longipalpus Montrouzier, 1861 (Coleoptera: Cerambycidae: Cerambycinae) from India with the description of a new species. 30 records from Visual Plants (144.41.33.158) - Private collection of Manfred Kueppers. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 281 records from NZCS Upper Tapanahony Expedition 1991. 5 records from Iberolygus n. gen., from the Iberian Peninsula (Hemiptera: Cimicomorpha: Miridae: Mirinae), with a new generic combination for Apolygus rubrostriatus (Wagner, 1971). 1 records from Oppia nitens. 15 records from Contribution to the Chinese Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae: Rhaphidophorinae): New species of Rhaphidophora Serville, 1838 from China. 24 records from Tanzanian Vertebrate Collection. 10 records from New species of Callichromatini Swainson, 1840. (Coleoptera, Cerambycidae). New Cerambycidae from Vietnam. Part 6. 41 records from Support for the underrepresented sex: new descriptions of scutacarid males (Acari, Heterostigmatina). 2 records from A new Neotropical genus of bee flies (Diptera, Bombyliidae, Phthiriinae). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 77 records from Terrestrial isopods of the genus Porcellio Latreille, 1804 (Isopoda; Oniscidea) in Iran, with a description of a new species. 5225 records from Las familias Polyporaceae sensu stricto y Albatrellaceae en México. 2 records from Cosmolaelaps Berlese (Mesostigmata: Laelapidae) from southern Brazil, with a new record of a heteromorphic male, description of a new species, and a key to the species reported from that country. 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 3 records from A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 10 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 2 records from Two New Variegated Snailfishes of the Genus Careproctus (Teleostei: Scorpaeniformes: Liparidae) from the Aleutian Islands, Alaska. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 2 records from A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia. 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 11344 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 5 records from Review of the genus Microcurgus Haupt, 1950 (Hymenoptera, Pompilidae) with description of a new species from Iran. 6619 records from Anfibios y reptiles del estado de Tamaulipas, México. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 13 records from Coleção de Coleoptera da Universidade de Brasília. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 714 records from Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): description of 10 new species from the L. australis, L. monteithi, and L. villosus species groups. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 585 records from Livingstone Museum Bat Collection. 1373 records from International Fossil Shell Museum (NL) - Mollusca Collection. 9 records from First records of Composetia, Eunereis and Nectoneanthes (Annelida: Nereididae) from Taiwan, with descriptions of two new species. 38 records from A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 4728 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 17 records from Reconsideration of the genera Merogomphus Martin, 1904, and Anisogomphus Selys, 1857, including erection of a new genus, with a new species and discussion of additional specimens from Cambodia. 199 records from Gastropods from the Cretaceous-Palaeogene boundary in Denmark. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 33782 records from CIRAD. 1 records from Cabamofa orientalis sp. nov. from Thailand, congeneric with C. mira Jaschhof from Costa Rica (Diptera: Bibionomorpha: Sciaroidea incertae sedis). 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 4 records from Two new species of Comesomatidae (Nematoda) from the East China Sea. 67 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 2740 records from Fungi specimens of Saitama Museum of Natural History. 2 records from A new species of Miobantia Giglio-Tos, 1917 with a novel morphological feature (Mantodea: Thespidae: Miobantiinae). 1129 records from Mollusca Collection of Saitama Museum of Natural History. 3 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 12 records from A new species of Conopsia Strand, 1913 (Lepidoptera: Sesiidae: Tinthiinae) from West Africa. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 25 records from Palaeoplex gen. nov. and Lufubuchromis gen. non, two new monotypic cichlid genera (Teleostei: Cichlidae) from northern Zambia. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 23 records from Kiwisaldula (Hemiptera: Heteroptera: Saldidae) from the South Island of New Zealand: new species and identification key. 12 records from Lance lacewings of the world (Neuroptera: Archeosmylidae, Osmylidae, Saucrosmylidae): review of living and fossil genera. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 4 records from Two new species of Bucculatrix Zeller (Lepidoptera: Bucculatricidae) from China. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 174 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 73091 records from Bell Museum fungi. 4 records from A needle in a haystack: the new genus Bernadottea (Diptera: Cecidomyiidae, Winnertziinae) with four new species in the Old World. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 120246 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 45 records from Redescription of the Indo-West Pacific cardinalfishes (Perciformes: Apogonidae) Rhabdamia spilota Allen & Kuiter 1994 and R. gracilis (Bleeker 1856). 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 20 records from Review of the leafhopper tribe Macrostelini Kirkaldy (Cicadellidae: Deltocephalinae) in Pakistan with description of a new species. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 15 records from Two new species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk, with a review of distinctive characters of the known species of the genus. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 12 records from Two new species of bent toed geckos, Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from Northeast India with comments on name-bearing types from the region. 8 records from Whip spiders (Amblypygi, Arachnida) of the Western Palaearctic—a review. 5995 records from Insect (HUNM-IN). 24 records from Sternaspis chilensis n. sp., a new species from austral Chilean channels and fjords (Annelida, Sternaspidae). 1 records from Damaeus auritus. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1 records from The ‘‘ Lembeh Frogfish’ ’ Identified: Redescription of Nudiantennarius subteres (Smith and Radcliffe, in Radcliffe, 1912) (Teleostei: Lophiiformes: Antennariidae). 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 15 records from Pupae of the Nearctic species of Culicoides Latreille subgenus Monoculicoides Khalaf (Diptera: Ceratopogonidae). 11208 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1288 records from Barcant Butterfly Collection - Nymphalidae. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 406575 records from Herbarium of Taiwan Forestry Research Institute. 2 records from Basothorhynchus, a new Oosomini genus from the highland plateau of Lesotho (Coleoptera: Curculionidae: Entiminae). 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 3 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 39 records from Revision of the Hoplodrina implacata group (Lepidoptera: Noctuidae: Noctuinae: Caradrinini) of Taiwan, with descriptions of four new species. 942 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25374 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 41 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 25 records from Annotated checklist of the fishes of the archipelago of Madeira (NE Atlantic): I-Chondrichthyes. 1 records from A new species of the Australian genus Clinopsocus New from coastal California (Psocodea: ‘ Psocoptera’: Elipsocidae). 604 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 6977 records from 2019_NSMK_PL_2. 8 records from New Hemilophini, Aerenicini and Calliini from French Guiana, transference and notes on Hemilophini (Coleoptera, Cerambycidae, Lamiinae). 53 records from Squid collection from 1995/96 V4 BROKE. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 126 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 11 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 98 records from The genus Pholetesor Mason, 1981 (Hymenoptera, Braconidae, Microgastrinae) from China, with descriptions of eleven new species. 8 records from A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 150 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 23 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part II. Genus Bradysiopsis Tuomikoski, 1960. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 3472 records from Microhabitat distribution of arboreal oribatid mites (Oribatida), associated with the Siberian pine (Pinus sibirica) of Western Siberia.. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 30078 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1 records from Oribates punctum. 13 records from A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 534 records from MEXU/Tipos de plantas vasculares. 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 4 records from Revision of the family Carabodidae (Acari: Oribatida) V (Fifth part). Redescription of Congocepheus latilamellatus Mahunka 1984, with complementary studies of C. ornatus, Mahunka 1983. Descriptions of Tanzaniacepheus gen. nov. and Zimbabwecepheus gen. nov.. 13 records from Bryozoa of the British Isles. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1284 records from Collection of Heteroptera. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 815 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 7 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 122 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 176 records from A checklist of the Robber Flies (Insecta: Diptera: Asilidae) of Wyoming, USA. 28187 records from UAZ Mammals. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 40 records from Geothermal Fumarole Subsurface Mt. Erebus, Antarctica. 2647 records from Actualización de la base de datos de colémbolos de México. 8 records from Order Diptera, family Mydidae. 336 records from Malawi-Saturniidae-Biodiversity-Data. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 245 records from Bird specimens of Obihiro Centennial City Museum. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1799 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 79 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 57270 records from Fish Specimens. 25 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 17713 records from NCSM Mammals Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 26 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 42521 records from VIC - Herbário da Universidade Federal de Viçosa. 139 records from Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 7 records from FIRST REPORT OF THE GENUS SESIEUTES SIMON (ARANEAE: LIOCRANIDAE) FROM CHINA, WITH DESCRIPTION OF ONE NEW SPECIES. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 2 records from Rediscovery of the holotypes of Mustela africana stolzmanni Taczanowski, 1881 (Carnivora: Mustelidae) and Cuniculus taczanowskii Stolzmann, 1885 (Rodentia: Cuniculidae) at the Museum and Institute of Zoology Polish Academy of Sciences in Warsaw, Poland. 377 records from Hydraenidae of Madagascar (Insecta: Coleoptera). 1 records from On the Chilopoda from Turkey. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 2 records from A new species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos. 176250 records from Arctic Ocean Diversity. 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 13 records from The dacnusine genus Chorebus Haliday (Hymenoptera: Braconidae: Alysiinae) from China. 2 records from New species of cynipid inquiline, Saphonecrus kuriphilusi (Hymenoptera: Cynipidae: Synergini), from Dryocosmus kuriphilus galls in Greece. 4207 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 151 records from CHAS Botany Collection (Arctos). 95 records from Código de barras de diferentes grupos de peces mexicanos endémicos de la Mesa Central Mexicana. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 59 records from Revision of Pyrrhalta (Coleoptera: Chrysomelidae: Galerucinae) species with maculate elytra. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 1 records from The genus AnTonia Loew in Egypt: A. gabalensis El-Hawagry, a new synonym of A. feDTschenkoi Loew (Antoniinae, Bombyliidae, Diptera). 1807 records from Données d'occurrence de la flore du Sénégal (Acanthaceae - Chenopodiaceae), Herbier IFAN. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from A review of the genus Paratus Simon (Araneae, Dionycha). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 4 records from Four new species of tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) from the Afrotropical Region. 3 records from New European records of Ditomyia macroptera Winnertz (Diptera: Ditomyiidae) with notes on its distribution. 10 records from Two new taxa of Plebejus Kluk, 1780 (Lepidoptera, Lycaenidae) from the Gobi desert, Mongolia. 9 records from Three new species of Aponuphis (Annelida: Onuphidae) from eastern Australia. 70229 records from The Fish Collection. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 55 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 4 records from A new Mediterranean species of Dolistenus (Diplopoda, Platydesmida, Andrognathidae), with an updated key for the genus and the first contribution for a barcode database of European Platydesmida. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102476 records from Denver Museum of Nature & Science - Entomology. 242 records from FBIP: Identification of polychaetes used as bait. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Entyposis cordipenis new species from Ethiopia (Coleoptera: Scarabaeidae: Melolonthinae: Schizonychini). 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 6 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 38841 records from Herbier de Strasbourg. 10212 records from Spider (NSMK-SP). 29246 records from OUPR - Herbário "Professor José Badini". 14 records from Current knowledge on Mexican tardigrades with a description of Milnesium cassandrae sp. nov. (Eutardigrada: Milnesiidae) and discussion on the taxonomic value of dorsal pseudoplates in the genus Milnesium Doyère, 1840. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 27 records from The genus Anaphothrips (Thysanoptera, Thripidae) in China, with three new species. 10650 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 6 records from Two new terrestrial species of Hydraena Kugelann from the island of Bioko, Gulf of Guinea (Coleoptera: Hydraenidae). 5 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 182 records from Revision of the ant genus Mayriella.. 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 168176 records from KUBI Mammalogy Collection. 24 records from New species of Thelepodidae (Terebelliformia, Polychaeta) from Taiwan. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 10270 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 201 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 15 records from Description of a new species of Pagurus Fabricius, 1775 (Crustacea: Paguroidea: Paguridae) from the Pacific coast of Costa Rica, Central America, with notes on Pagurus albus (Benedict, 1892). 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 5 records from ------ A- ----- new- ----- species- ----- of- ----- the- ----- genus ------ Toleria- ----- Walker, ------ [1865] ------ from- ----- northern ------ Vietnam- ----- and Laos- ----- with- ----- establishment- ----- of- ----- a- ----- new- ----- generic ------ synonymy- ----- in- ----- Cissuvorini- ----- (Lepidoptera Sesiidae). 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from Description of Coeliccia bhriulieci sp. nov. (Odonata: Zygoptera: Platycnemididae) from central Vietnam. 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 26 records from Pachyprotasis kojimai sp. nov. — the “ Pachyprotasis nigronotata ” of Japanese authors (Hymenoptera: Tenthredinidae). 3 records from Two new species of Sphaeronemoura (Plecoptera: Nemouridae) from Oriental China. 3139 records from Sammlung Clemens Borneo Herbarium Hamburgense HBG. 1 records from A new species of Trimma (Pisces; Gobiidae) from the South-West Islands of Palau, western Pacific Ocean. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 2 records from Holorchis castex n. sp. (Digenea: Lepocreadiidae) from the painted sweet-lips Diagramma pictum (Thunberg, 1792) (Perciformes: Haemulidae) from New Caledonia. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from A new species of the thorid genus Paralebbeus Bruce & Chace, 1986 (Crustacea: Decapoda: Caridea) from the deep sea of the Northwestern Pacific Ocean. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 15 records from The new Southeast Asian genus Cambonilla gen. nov. (Zodariidae, Araneae): ‘ bis repetita placent’. 43770 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 3 records from A new, remarkable erigonine spider genus from eastern Asia (Araneae, Linyphiidae). 143 records from A review of the spider genus Porrhomma (Araneae, Linyphiidae). 29864 records from Rutgers University, Chrysler Herbarium. 6 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 36162 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 9488 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 3 records from Three new species of the subgenus Ashima (Diptera: Drosophildae: Phortica) from southwestern China, with DNA barcoding information. 239 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 5 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 352692 records from Plantae of Costa Rica (INBio). 1 records from Nothrus runcinatus. 56942 records from Annelida collection of National Museum of Nature and Science. 2 records from The webspinning sawfly genus Neurotoma (Hymenoptera, Pamphiliidae) of South Korea: Neurotoma silla sp. nov. and a key to species. 6 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 1 records from A new species of Macrosaccus (Lepidoptera: Gracillariidae: Lithocolletinae) from Arizona, USA. 97 records from The Coccinellidae (Coleoptera) from Fuerteventura, Canary Islands. 17 records from A New Species of Flea of the Genus Kohlsia Traub, 1950 (Siphonaptera: Ceratophyllidae) from Veracruz, Mexico. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 55 records from Review of the Priocnemis hyalinata species-group (Hymenoptera: Pompilidae), with description of a new species from China. 11686 records from Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosques secos Colombianos de la Colección Entomológica del Instituto Alexander von Humboldt. 494 records from Análisis de Integridad Biológica para el Parque Natural Regional Páramo del Duende. Convenio CVC- Univalle 108 de 2017. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 9 records from Empidoid flies from Cabo Verde (Diptera, Empidoidea, Dolichopodidae and Hybotidae) are not only composed of Old World tropical species. 26 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 440 records from Wichita State University Collection. 595 records from La liste (3) Rouge des plantes menacées de la Guinée. 4 records from Two new species of the genus Phytocoris (Hemiptera: Miridae), with a revised identification key to species of the subgenus Compsocerocoris found in Iran. 19 records from A new species of Micrathyria Kirby, 1889 from México and Central America (Anisoptera: Libellulidae), with a key to Mexican species. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 398 records from Tsetse flies of East Africa update. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 3682 records from Flora of Sumatra : Vascular plant collection from Batang Toru Forest deposited in ANDA Herbarium. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 1 records from Amphibia ZMK. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 3 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20755 records from pins. 1005 records from Collection Crustacea - KAUMM. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 772 records from FBIP: Baboon spider distribution records from selected South African museums. 1 records from Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 3 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 49 records from Mammal specimens of Natural History Museum, Kishiwada City. 381 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 55849 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 2 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 11129 records from Royal Ontario Museum Fungarium (TRTC). 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 66 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 23 records from Pachyrhynchus elenae Rukmane, 2016, a new synonym of Pachyrhynchus phaleratus Waterhouse, 1841 (Coleoptera: Curculionidae: Entiminae). 14052 records from Plant specimens of Horaiji-san Museum of Natural History. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 6 records from Taxonomic status of the barbastelles (Chiroptera: Vespertilionidae: Barbastella) from the Japanese archipelago and Kunashir Island. 4 records from Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 43598 records from Mammals housed at MHNG, Geneva. 12 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 14 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 45 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from Spockia tagala gen. and sp. nov. a new monotypic genus of Asopinae (Hemiptera: Heteroptera: Pentatomidae) from the Philippines. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 225 records from UWIZM Mantodea. 5 records from A new and five rare bdelloids from Korea. 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 10 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 7 records from Review of the Oriental leafhopper gen
Keywords: GBIF; biodiversity; species occurrences